2009
DOI: 10.1097/mej.0b013e32832a0864
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of brain trauma patients who have a Glasgow Coma Scale score of 3 and bilateral fixed and dilated pupils in the field

Abstract: Patients with a GCS of 3 and BFDP in the field should be resuscitated aggressively, especially if the trauma seems to be not too severe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 17 publications
2
21
0
4
Order By: Relevance
“…[19][20][21][22][23][24][25][26][27][28][29][30][31] However, these research findings are mixed. [19][20][21][22][23][24][25][26][27][28][29][30][31] Our study focused on the specific executive functions deficit in SA after TBI, which not been well studied with regard to gender. The study purpose was to examine (1) possible gender differences in SA of injury-related deficits and (2) possible causes for these gender differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23][24][25][26][27][28][29][30][31] However, these research findings are mixed. [19][20][21][22][23][24][25][26][27][28][29][30][31] Our study focused on the specific executive functions deficit in SA after TBI, which not been well studied with regard to gender. The study purpose was to examine (1) possible gender differences in SA of injury-related deficits and (2) possible causes for these gender differences.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] Mixed findings are typical in studies comparing broad post-TBI outcomes for men and women. [19][20][21][22][23][24][25][26][27][28][29][30][31] On the one hand, research has shown that women with TBI outperform men in executive functions, 1 working memory, 27 delayed visual memory, 20 and written language, 21 as well as in rehabilitation outcomes 21 and community integration. 22,23 Investigators have also noted that women are more likely to survive their injuries and less likely to have postinjury complications than men.…”
mentioning
confidence: 99%
“…The animal and human brain injury literatures chronicle high scientific interest in a possible female gender advantage in recovery from traumatic brain injury (TBI) based on sex hormone neuroprotection (Groswasser, Cohen, & Keren, 1998;Kokiko, Murashov, & Hoane, 2006;Mauritz et al, 2009;Niemeier, Marwitz, Lesher, Walker, & Bushnik, 2007;Stein, 2001;Stein & Wright, 2010;Wagner et al, 2004). One rationale is that progesterone is neuroprotective following TBI, prompting clinical trials on the efficacy of exogenous administration acutely (Davis & Hoyt, 2006;Farin, Deutsch, Biegon, & Marshall, 2003;Gordon et al, 2006;Parks, Diaz-Arrastia, Gentilello, & Shafi, 2010;Slewa-Younan, van den Berg, Baguley, Nott, & Cameron, 2008;Stein & Wright, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Despite their overall dismal prognosis, some patients with a traumatic intracranial hematoma who present with a GCS score of 3 and fixed and dilated pupils can survive with treatment. [14][15][16] Moreover, survival and even functional neurological recovery has been reported following predominantly medical reversal of transtentorial herniation secondary to a supratentorial mass lesion from a variety of causes. [17][18][19] Survival with good outcome has even been reported after advanced cerebral herniation with Duret hemorrhage (a secondary brainstem hemorrhage that results from stretching and rupture of pontine perforating vessels during herniation), a condition commonly linked with brain death.…”
Section: Discussionmentioning
confidence: 99%